Single-Cell Transcriptomic Profiling of Human Dental Pulp in Sound and Carious Teeth: A Pilot Study - Opasawatchai, Anunya; Nguantad, Sarintip; Sriwilai, Benjamaporn; Matangkasombut, Ponpan; Matangkasombut, Oranart; Srisatjaluk, Ratchapin; Charoensawan, Varodom (Frontiers in Dental Medicine, 2022)
A comprehensive understanding of dental pulp cellular compositions and their molecular responses to infection are crucial for the advancement of regenerative dentistry. Here, we presented a pilot study of single-cell transcriptomic profiles of 6,810 pulpal cells isolated from a sound human maxillary third molar and three carious teeth with enamel and deep dental caries. We observed altered immune cell compositions of the dental pulp in deep, but not enamel ones. Differential expression analysis revealed up-regulation of several pro-inflammatory, anti-inflammatory, and mineralization-related genes in the immune and stromal cells of the deep dental caries. Making use of an algorithm for predicting cell-to-cell interactions from single-cell transcriptomic profiles, we showed an increase in cell-cell interactions between B cells, plasma cells and macrophages, and other cell types in deep dental caries, including those between TIMP1 (odontoblasts) – CD63 (myeloid cells), and CCL2 (macrophages) - ACKR1 (endothelial cells). Collectively, our work highlighted the single-cell level gene regulations and intercellular interactions in the dental pulps in health and disease.